2015
DOI: 10.24123/jmb.v14i1.307
|View full text |Cite
|
Sign up to set email alerts
|

Professional Commitment of Accountant and the Commitment of Public Accounting Firms on Auditor’s Job Satisfaction

Abstract: The Public Accounting Firms (PAFs) have notoptimally met their user’s expectation in providing high quality auditings services. Many financial scandals that involve public accounting practitioners are still occurring. They make users of auditing service confuse about integrity of Certified Public Accountants. This study aims to obtain empirical evidences in evaluating of the extent to which the professional commitment of accountant and organizational PAFs commitmenaffecton auditor’s job satisfaction. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
1
0
1
Order By: Relevance
“…As the professional commitment of independent auditors increases, the quality of the audit also increases. These results are compatible with the literature (Tandiontong, 2013;Selimoğlu & Yeşilçelebi, 2014). In addition, according to the study model, technostress concluded that the effect of organizational stress on individual work performance and audit quality can be measured with the occupational dependence moderator.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As the professional commitment of independent auditors increases, the quality of the audit also increases. These results are compatible with the literature (Tandiontong, 2013;Selimoğlu & Yeşilçelebi, 2014). In addition, according to the study model, technostress concluded that the effect of organizational stress on individual work performance and audit quality can be measured with the occupational dependence moderator.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, auditors with high professional commitment are expected to be less likely to sign financial statements that are materially misrepresented, which can have a significant impact on the quality of the independent audit activity performed (Lord & DeZoort, 2001;Selimoğlu & Yeşilçelebi, 2014;Smith & Hall, 2008). In this context, studies examining the effect of professional commitment on the quality of independent auditing revealed that the quality of independent auditing increases as the level of professional commitment of independent auditors increases (Selimoğlu & Yeşilçelebi, 2014;Tandiontong, 2013). There are studies in the literature that found professional commitment has a positive relationship with audit quality (Lestari et al, 2020;Leo Handoko et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Kompetensi auditor menentukan peluang untuk mendeteksi kesalahan yang ada pada laporan keuangan (DeAngelo 1981). Sedangkan independensi berhubungan dengan sejauh mana auditor dapat bersikap independen dalam melakukan proses audit dan memberikan opini audit (Tandiontong 2015).…”
Section: Kualitas Auditunclassified